2017
DOI: 10.58221/mosp.v111i1.7789
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding writing development: How formative is the feedback?

Abstract: This paper contrasts students’ perceptions of feedback practices on written texts and their utilization of the feedback against formative assessment pedagogy. It uses observations of nine lessons of English writing in combination with semi-structured interviews of 39 first year upper secondary students in Norway. The findings show that students in general appreciate the feedback, but have diverging views about the different types and forms of feedback provided. The majority want to have one-to-one discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…The non-significant differences between the four subsamples suggest consistency in how students perceive product-based feedback techniques and which ones they prefer to receive from instructors, regardless of their different academic years. In contrast to the present study’s findings regarding WF modes , the teacher as the sole source of WF was highly preferred in the study conducted by Saliu Abdulahi [ 63 ]. The present study’s findings regarding WCF echoed those of Ouahidi and Lamkhanter [ 37 ] and those of Sinha and Nassaji [ 27 ], who found that the majority of the students received direct WCF from their teachers.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…The non-significant differences between the four subsamples suggest consistency in how students perceive product-based feedback techniques and which ones they prefer to receive from instructors, regardless of their different academic years. In contrast to the present study’s findings regarding WF modes , the teacher as the sole source of WF was highly preferred in the study conducted by Saliu Abdulahi [ 63 ]. The present study’s findings regarding WCF echoed those of Ouahidi and Lamkhanter [ 37 ] and those of Sinha and Nassaji [ 27 ], who found that the majority of the students received direct WCF from their teachers.…”
Section: Discussioncontrasting
confidence: 84%
“…Similar to the present study’s findings regarding a technique for effective WF modes , Elwood and Bode [ 18 ] and Leki [ 96 ] found that detailed feedback with support and guidance was more utilized by the students in their study. Unlike its moderate use in this study, judgmental WF , which is based on assessment criteria during the writing process, was not frequently used according to Saliu Abdulahi’s [ 63 ] study. The findings of Saliu Abdulahi [ 63 ] were also not in harmony with those of the current study, where students have a moderate use of self-assessment when developing evaluative judgment because they regularly self-evaluated their written text before submitting and before receiving the grade, or after looking at the teacher’s assessment criteria that helped them in their writing assignment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found that teachers used feedback merely for the identification of errors and making corrections, rather than a reflective and critical understanding of learners. However, the literature indicates that feedback is not a surface-level activity rather it is a systematic and rigorous process of engaging teachers and students in the learning process (Saliu, 2017). Teachers have a leading role in this whole exercise.…”
Section: Discussionmentioning
confidence: 99%